Exergy analysis of thermal energy storage options with nuclear power plants. (October 2016) - Edwards, Jacob; Bindra, Hitesh; Sabharwall, Piyush
Highlights: Different thermal energy storage (TES) methods are proposed for small modular nuclear reactors. Exergy and energy density analyses of TES integration with NPPs are conducted and presented. Sensible heat liquid-type TES systems outperform solid-type systems. Abstract: Storing excess thermal energy in a storage media, that can later be extracted during peak-load times is one of the better economic options for nuclear power in future. Thermal energy storage integration with light-water cooled and advanced nuclear power plants is analyzed to assess technical feasibility of different options. Various choices of storage media considered in this study include molten salts, synthetic heat transfer fluids, and packed beds of solid rocks or ceramics. Due to limitations of complex process conditions and safety requirements there are only few combinations which have potential integration possibilities. In-depth quantitative assessment of these integration possibilities are then analyzed using exergy analysis and energy density models. The exergy efficiency of thermal energy storage systems is quantified based on second law thermodynamics. This study identifies, examines, and compares different energy storage options for integration with modular NPPs, with the calculated values of energy density and exergy efficiency. The thermal energy storage options such as synthetic heat transfer fluids perform well for light-water cooled NPPs, whereas liquid storage salt show better performance with advanced NPPs as compared to other options.